SUSTAINABLE DEVELOPMENT MANAGEMENT AND TRANSFRORMATION OF PLANNED ECONOMY TO MARKET ECONOMY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
In the article the main requirements for sustainable economic development management system were formed using theoretical approach. According to the collected theoretical material, approaches of sustainable management of economic systems from the viewpoint of principles of sustainability are reviewed. The article evaluates the content and issues related to the environmental indicators, including the environmental space and the ecological footprint concepts, applied in sustainability measurement, as well.